PERSEPSI MAHASISWA TERHADAP PENGEMBANGAN KEGIATAN BADAN EKSEKUTIF MAHASISWA DI FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI JAKARTA - Mutakim, Jaenal (EMPOWERMENT : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2015)
Fostering good student will produce a synergy effect in achieving success at school and university education. Fostering good students will generate ideas, support, problem solving, and the ability to make good decisions for students in the future. Student Organizations UNJ FIP is a vehicle for personal development of students who are expected to accommodate the needs, interests and talents-indulgence, to improve the welfare and well as container building activities and scientific reasoning as well as the direction of the profession students. Students showed high perception in terms of expressing their aspirations in the form of elections conducted to choose a new head. High perception of the existence of a transparent process in elections organized by BEM. Awareness of the need to convey the aspirations and processes that take place in a transparent and fair is a manifestation of the student's concern for the development of talent and interest in the Faculty of Education UNJ. Recommendations can be submitted on students' perceptions of the development activities of the Student Executive Board is necessary to set up a communication forum between students with BEM / HIMA through more open containers.